1996
DOI: 10.1016/0014-2999(96)00058-1
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of acetylcholine or dopamine receptors in the nucleus accumbens differentially alters dopamine release in the striatum of freely moving rats

Abstract: The present study examined whether unilateral stimulation of acetylcholine or dopamine receptors in the nucleus accumbens induces an asymmetry in dopamine transmission in the ventrolateral striatum. For this purpose, a microdialysis technique was used to measure dopamine release in both sides of the ventrolateral striatum following unilateral injections of carbachol (5 ¿¿g/0.5 j j l \ ) or a mixture of dopamine Dj and dopamine D 2 receptor agonists (l-phenyl-2,3,4,5-tetrahydro-ltf-3-benzazepine-7,8-diol 5 fig … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Recently, it has been found that this type of turning when elicited from the nucleus accumbens is inhibited by blockade of dopamine receptors in the ventrolateral striatum (Saigusa et al 1993(Saigusa et al , 1995. Moreover, the accumbens stimulation also enhances dopamine release in that part of the striatum (Koshikawa et al 1996). These data strongly suggest that the turning elicited from the shell is somehow funnelled via the ventrolateral striatum.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, it has been found that this type of turning when elicited from the nucleus accumbens is inhibited by blockade of dopamine receptors in the ventrolateral striatum (Saigusa et al 1993(Saigusa et al , 1995. Moreover, the accumbens stimulation also enhances dopamine release in that part of the striatum (Koshikawa et al 1996). These data strongly suggest that the turning elicited from the shell is somehow funnelled via the ventrolateral striatum.…”
Section: Discussionmentioning
confidence: 92%